Robustness of the healthcare utilization results from the Rotavirus Efficacy and Safety Trial (REST) evaluating the human-bovine (WC3) reassortant pentavalent rotavirus vaccine (RV5) - Van Damme Pierre; Gothefors Leif; Matson David O; Koch Gary; Itzler Robbin; DiNubile Mark J; Heaton Penny M (BMC, 2010)
Abstract Background The Rotavirus Efficacy and Safety Trial was a placebo-controlled Phase III study that evaluated the safety and efficacy of a three-dose pentavalent rotavirus vaccine (RV5) including its effect on healthcare utilization for rotavirus gastroenteritis (RVGE). The per-protocol (PP) analyses, which counted events occurring 14 days after dose 3 among infants without protocol violations, have already been published. This paper evaluates the consistency of the healthcare utilization results based on the modified intention to treat (MITT) analyses with the PP analyses. The MITT analyses include all infants receiving at least one dose of vaccine or placebo and follow-up begins after dose 1. The paper also explores the consistency of the results for different subgroups of the study population with different types of surveillance. Methods Data on healthcare utilization for acute gastroenteritis were collected via telephone interviews after administration of the first dose. Parents were either contacted every 6 weeks or every 2 weeks depending on the substudy in which they were enrolled. Those contacted every 2 weeks were also asked to complete symptom diaries. Poisson regression was used to evaluate the effect of RV5 on the rates of RVGE-associated healthcare encounters in all of the analyses. Results In the first 2 years after vaccination, RV5 reduced the combined rate of hospitalizations and emergency department (ED) visits 88.9% (95% CI: 84.9, 91.9) for all RVGE regardless of serotype in the MITT analysis compared with a 94.5% (95% CI: 91.2, 96.6) reduction based on the G1-G4 PP analysis. By type of surveillance, the rate reductions for the G1-G4 PP analysis were 91.0% (95% CI: 81.7, 95.5) and 95.9% (95% CI: 92.2, 97.8) among parents contacted every 2 weeks (number evaluable = 4,451) and every 6 weeks (number evaluable = 52,683) respectively. Conclusions Our analyses demonstrated that the effect of RV5 on reducing the rate of hospitalizations and ED visits based on the MITT analyses were generally consistent with the PP analyses. The rate of events for subgroups with different intensities of surveillance differed but the effect of RV5 on the relative rate reductions were consistent with the results that have already been published. Trial Registration ClinicalTrials.gov number, NCT00090233